Inviolability Under Fire: The 2024 Israeli Attack On Iranian Consular Premises And Syria’s State Responsibility Under Diplomatic Law - Galio Parly Keliat Galio; Sutiarnoto; Fajar Khaify Rizky (Talenta Publisher, Universitas Sumatera Utara, 2025)
The attack on Iran’s consular premises in Damascus underscores significant legal challenges concerning the special duty of the receiving State to protect foreign representations. In international law, the protection of diplomatic and consular missions is a fundamental obligation of the receiving State, as regulated under the 1961 Vienna Convention on Diplomatic Relations and the 1963 Vienna Convention on Consular Relations. This research aims to analyze the obligations of Syria, as the receiving State, in protecting the consular premises of Iran in Damascus from third-party attacks based on diplomatic law. This research employs a normative legal research method with a descriptive approach, utilizing an analysis of international legal instruments, legal doctrines, and relevant State practices. The results indicate that Syria, as the receiving State, failed to fulfill its obligation to take all appropriate steps to protect the inviolability of the consular premises and the safety of consular officers. Such failure constitutes a breach of the protective obligations stipulated in Article 22 paragraph (2) of the 1961 Vienna Convention and Article 31 paragraph (3) of the 1963 Vienna Convention, specifically regarding the receiving State's duty to prevent any form of attack, damage, or disturbance of the peace of the consular mission. This research provides an academic contribution by strengthening the understanding of the nature of the receiving State's obligations in the context of consular protection as an obligation of conduct, as well as a practical contribution in affirming the standards of State responsibility within the context of modern armed conflict under diplomatic law.